Assessing the Impacts of Parenting Styles on Academic Achievement in Early Childhood Education and Development in Narok South Sub - County, Kenya - shinali, Mary Consolata; Koech, Peter Kibet (International Journal of Research in Education and Social Science, 2016)
The study sought to assess the impact of parenting styles on academic performance in Early Childhood Education Service in Narok South Sub County. The study was conducted in public primary schools in Narok County using descriptive survey. Qualitative and Quantitative data collection techniques were combined for the study. The instruments for the study included questionnaires, observation checklist and structured interview. Purposive sampling was used in the selection of the population. 50 respondents from 20 ECDE centers were selected for the study. After analyzing data, it was presented in tabular and graphical form. The researcher established that parenting styles have an impact on the academic achievement of learners at the ECDE level. Parents and the community at large should be sensitized on the effects of parenting styles on the young children. The result and findings of the study yielded data and information that would be of importance to the policy makers on how they can involve parents in seminars and workshops on life skills. It would also inform them on the need to strike a balance between high handedness and acceptable parenting styles for the good of the young children.
Keywords: Parenting style; Authoritative; Authoritarian; Permissive; Uninvolved parenting